Educação ambiental: um caminho para o desenvolvimento sustentável - Lopes, Izabela Cristina [UNESP]; Costa, Maria Angélica Martins [UNESP]; Sarti, Arnaldo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Environmental education emerged from the worsening of the environmental problems that caused the need to change the relationship between man and nature. Thus, it’s so important to discuss about this issue especially with children, because they are the responsible for the future of the planet. Therefore, this project intends to bring environmental education for children of kindergarten, in view of the importance of changing human habits towards nature.

A educação ambiental surgiu do agravamento dos problemas ambientais que desencadearam a necessidade da mudança na relação homem-natureza. Assim, é imprescindível a discussão da importância deste tema especialmente com as crianças, pois elas são as responsáveis pelo futuro do planeta. Portanto, o projeto em questão pretendeu levar a educação ambiental para crianças do ensino infantil, tendo em vista a importância da mudança de hábitos humanos frente a natureza.
Keywords: Environment; Education; Children; Meio ambiente; Educação; Crianças